2020
DOI: 10.1177/2381468320963781
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning Shared Decision Making: A Reflection for the Next Decade

Abstract: Despite the evolving evidence in favor of shared decision making (SDM) and of decades-long calls for its adoption, SDM remains uncommon in routine care. Reflecting on this lack of progress, we sought to reimagine the future of SDM and the path to take us there. In late 2017, a multidisciplinary and international group of six researchers were challenged by a senior SDM scholar to envision the future and, based on a provocatively critical view of the present, to write letters to themselves from the year 2028. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…In general, across both care settings, women appear to rate the midwife’s empathy better than the midwife’s SDM behavior. Although SDM effects are well documented in health services research and the concept is considered a central component of high-quality patient care, implementation in routine care is lacking [ 55 ]. SDM is often considered an add-on to discipline-specific care delivery in the care setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, across both care settings, women appear to rate the midwife’s empathy better than the midwife’s SDM behavior. Although SDM effects are well documented in health services research and the concept is considered a central component of high-quality patient care, implementation in routine care is lacking [ 55 ]. SDM is often considered an add-on to discipline-specific care delivery in the care setting.…”
Section: Discussionmentioning
confidence: 99%
“…SDM is often considered an add-on to discipline-specific care delivery in the care setting. Here, clarification is needed on whether the use of standardized procedures can simplify SDM processes and facilitate the efficiency of procedures to ensure women’s rights [ 55 ]. This marks a starting point for clinical practice to align maternity care more closely with women’s needs [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Patient Information Forum reported that in the UK, 1.7 million people are unable to explain symptoms or feelings on the phone [ 22 ]. This is likely to impair the quality of patient-clinician shared decision-making and widen existing health inequalities and these challenges are likely amplified by low health or digital literacy, hearing, visual, or cognitive impairment or language barriers [ 23 26 ], commonly experienced by older adults [ 6 ]. Studies have continued to highlight patient and clinician preferences for face-to-face consulting, with evidence that clinicians want to see and examine patients with RA [ 21 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 I was participating in shared decision making, which, although promoted for decades, remains uncommon in routine care. 22 Materials for clinicians are readily available (such as the USPSTF guidelines on shared decision making and decision aids), 23 but there are impediments such as economic constraints and determining which interventions warrant shared decision making in busy practices. 24,25 Sufficient consultation time, increasingly in short supply, is a necessity.…”
Section: How To Integrate Uncertainty In Clinical Practicementioning
confidence: 99%